(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The first step in achieving this goal is to have an educated workforce. Governments all aroundthe globe want their nations to have high-value and high-skill economies. A person’s capacity for learning,processing information, and applying knowledge to specific or local circumstances is developed viaeducation. As a result, it offers the basis for constructing knowledge in an information-based society.Analyzing the impact of government expenditure on India’s economic development in this perspective isintriguing. The current research used GDP as a proxy for economic growth and total governmentspending on education as a proxy for the knowledge economy to examine the impact of educationspending on economic development in India. The study supports the existence of a beneficialassociation between educational spending and academic outcomes.